2016
DOI: 10.1039/c6nj01187j
|View full text |Cite
|
Sign up to set email alerts
|

Slipped-cofacial J-type phthalocyanine dimers as potential non-linear absorbers for optical limiting applications

Abstract: Phthalocyanine J-type dimers show unusual spectral properties and self-assembly in the solid phase. The optical power limiting effect was theoretically investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…The calculated absorption spectra of isolated organic dyes under different electric fields demonstrate significant variation in the spectral region of transparency. The simulated optical response as the “transmittance vs. field strength” relationship shows a tendency toward optical limiting similar to what is usually observed in practice. To bring theory and practice closer together, primarily, one should compare the oscillation strength of the TDDFT transitions and the absorption coefficient of the dyes in solution or a matrix. Then, one can operate with such macroscopic parameters as linear transmission and optical layer thickness.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…The calculated absorption spectra of isolated organic dyes under different electric fields demonstrate significant variation in the spectral region of transparency. The simulated optical response as the “transmittance vs. field strength” relationship shows a tendency toward optical limiting similar to what is usually observed in practice. To bring theory and practice closer together, primarily, one should compare the oscillation strength of the TDDFT transitions and the absorption coefficient of the dyes in solution or a matrix. Then, one can operate with such macroscopic parameters as linear transmission and optical layer thickness.…”
Section: Introductionmentioning
confidence: 53%
“…In the experiment, the optical limiting effect is observed as a decrease in transmission on the growth of the radiation power, when the sample is placed at the focus of a collecting lens. , At the same time, it was shown that the optical effect observed in laser experiments can be reproduced using ab initio calculations . For this purpose, TDDFT calculations are performed by perturbing the ground state with electric fields polarized in all Cartesian directions . Thus, the electrical component of laser radiation is associated with a series of electric fields in simulation.…”
Section: Introductionmentioning
confidence: 99%
“…[20] On the other hand, aggregation is known to enhance nonlinear optical properties of phthalocyanines improving their efficiency as optical limiters. [21][22][23][24] In the present work we showed how aggregation of benzoannelated phthalocyanines can be controlled by variation of functional groups at distant positions with respect to the tetrapyrrolic core. These results can contribute to elaboration of phthalocyanine-based materials with tuneable properties.…”
Section: Discussionmentioning
confidence: 61%
“…The aggregation of Pcs, on the other hand, can have an uncontrolled and unforeseeable effect on the photophysical properties and considerably influences these properties as well. For example, absorption, fluorescence quantum yield and photosensitizer activity of Pcs may drastically decrease upon aggregation . In general, aggregation can be divided into two different types (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, absorption, fluorescence quantum yield and photosensitizer activity of Pcs may drastically decrease upon aggregation. [2] In general, aggregation can be divided into two different types (Figure 1). On one hand, tetrapyrrol macrocycles can form face to face aggregates with the molecular transition dipole moments connected perpendicular to the line connecting their centres.…”
Section: Introductionmentioning
confidence: 99%